Potential of Meat Substitutes for Climate Change Mitigation and Improved Human Health in High-Income Markets - Ritchie, Hannah; Reay, David S.; Higgins, Peter (Frontiers in Sustainable Food Systems, 2018)
The global food system contributes approximately one-quarter of greenhouse gas (GHG) emissions, with these dominated by the livestock sector. The projected increase in livestock demand is likely to undermine efforts to keep global average warming below a 2°C target. A carbon tax is often proposed as the preferred demand-side mechanism for reduced meat consumption. Previous studies, however, suggest that while this could prove successful in reducing net global emissions, it may worsen nutritional standards in lowest-income nations. An alternative market mechanism which may simultaneously reduce GHG emissions and improve health at all income levels is a reduction in the price of meat substitute products (meat-free proteins with particular nutritional and aesthetic similarities to meat). Using a combined ecological and health modeling approach, we project the associated GHG savings and health benefits associated with a stepwise reduction in the price of meat substitute products. Utilizing food demand elasticities, we quantify the substitution of meat commodities across a range of social acceptability scenarios. Our results show that meat substitute products—integrated within a “flexitarian” approach (primarily vegetarian but occasionally eating meat and fish)—have a large potential for reducing GHG emissions (up to 583 MtCO2e per year) and improving nutritional outcomes (up to 52,700 premature deaths avoided per year). However, this capacity is strongly dependent on a combination of price reductions and improved social acceptability of this product group; therefore both will be essential.